Caracterização da morfoanatômia, fenologia e composição química do óleo essencial de Aloysia hatschbachii (Verbenaceae) - Araujo, Guilherme Masarro (2020)
Research efforts to determine essential oil contents in aromatic plants can be a valuable tool, since essential oils may contain substances of interest not only for agriculture but also for pharmacology, perfumery and the health sector alike. Therefore, investigating and giving a detailed description of a given species optimizes activities such as management and contributes information about plant structure, best time of harvest and best oil extraction method. The objective of this study is thus to describe the morphoanatomy of leaf, flower, fruit, stem and root structures, the phenology (phenophases) and also the essential oil composition and yield of Brazil’s native endemic species Aloysia hatschbachii (Moldenke). The study was conducted in an experimental site of the Federal University of Santa Maria, Frederico Westphalen Campus, in Rio Grande do Sul state, over the period between 2018 and 2019. Adult plants were used for the morphological and anatomical descriptions. Portions of mature leaf, flower, fruit, stem and root tissues were subjected to a dehydration process, then embedded in HistoResin to obtain histological sections and later stained with toluidine blue and photomicrographed in the Laboratory of Wood Anatomy to identify the main anatomical structures, using a scanning electron microscope. For the morphological structures, pictures were taken from on-site sample specimens, depicting also small structures such as flowers with the help of a 4X magnifying lens. For the phenological description, five plant specimens were evaluated by measuring both the percent index of intensity and the index of activity of different phenophases, referred to as budding, mature leaves, leaf senescence, leaf fall, flowering and fruiting phases. The plant specimens were propagated vegetatively using plant cuttings in quantity sufficient to extract essential oil using a modified Clevenger apparatus. After three hours of boiling, the resulting essential oil was collected and sent to the Laboratory of Plant Extracts of the Federal University of Santa Maria to undergo gas chromatography analysis. The identification of components was based on both the retention index and concentration of each constituent, using the total area of its peak in comparison with the total area of all peaks. The analysis showed that leaves in this species are incomplete, simple and positioned predominantly in an opposite decussate arrangement but sometimes arranged in whorls, having a papery texture and serrated edge with nine pairs of teeth, being densely covered with hairs, and showing glandular and non-glandular trichomes, with anomocytic stomata on the abaxial surface. Stems are densely covered with hairs, have a peeling bark, with the pith parenchyma containing starch reserves and fiber bundles distributed around the stem. Inflorescences are racemose, with small bracts accompanying each purple-white flower, have superior ovary and are densely covered with hairs. These morphoanatomical characteristics show that plant organs such as leaf, leaf petiole, stem and flower structures are densely covered with trichomes. Phenologically, this species was found to be non-deciduous, holding mature leaves throughout the entire cycle, there also being correlations between phenophases and meteorological variables. The essential oil present in the trichome structures was found to have components of interest to the pharmaceutical and health sector, with a satisfactory yield. The essential oil from Aloysia hatschbachii predominantly consists of sesquiterpenes such as β-Elemene and Germacrene B, but also has monoterpenes and phenylpropanoids, though in lower concentrations. It can be concluded that the species Aloysia hatschbachii presents characteristics of the botanical genus Aloysia, such as the presence of trichomes, with characteristics of non-deciduos leaves and phenology influenced by climatic variables, and production of essential oil with high concentration of sesquiterpenes (above 84%) and its potential antimicrobial action.